Students’ Speaking Strategies in English Lesson At Vocational High School of Ma’arif V Kebumen - Firharmawan, Hastri; Rahmawati, Aulia; Nurhidayat, Eka (English Education and Literature Journal (E-Jou), 2023)
Speaking strategies play a vital role in enhancing communication skills and promoting meaningful engagement between speakers and their audiences. This research was aimed to investigate the both direct and indirect strategies used by students in order to succeed in their speaking lesson in English subject. The survey design was used in the research. The researcher gathered quantitative, numbered data via one-on-one questionnaires and interviews; and then, statistically analyzed the data to describe trends regarding question responses to answer the research questions. The samples were 60 students at the 12th grade of SMK Ma’arif V Kebumen in the academic year of 2022/2023. The survey revealed that in order to develop their speaking abilities, the students have adopted a number of direct and indirect speaking strategies. These strategies addressed a variety of areas, such as memory, cognition, compensation, metacognition, affective, and social interaction. Direct strategies are those that are explicitly taught to students. These include things like rehearsal, using visual, and using a dictionary. Indirect strategies are those that are not explicitly taught, but that students learn through experience. These include things like using planning, finding a speaking partner, and using humor. The study suggested that a combination of direct and indirect strategies can be effective in improving speaking skills. Teachers should consider using a variety of strategies to help their students improve their speaking skills. Keywords: Direct strategies, indirect strategies, speaking skills